"Smart" passive thermal insulation of confined natural convection heat transfer: An application to hollow construction blocks. (September 2017) - Idan, Shahar; Feldman, Yuri
Highlights: The concept of "smart" thermo-insulating materials is generalized. The concept is applied to thermal insulation of hollow construction blocks. The geometry of the optimized porous materials is determined. The same insulating efficiency is reported for hot and cold weather conditions. Abstract: A method for the design of "smart" passive thermo-insulating materials based on the statistical evaluation of the confined natural convection flow in the presence of heterogeneous porous media is presented. An application of the method for the enhancement of the insulating efficiency of hollow construction blocks is discussed. Confined natural convection flow developing inside a differentially heated cavity (comprising a convenient model for the air filled cavity in the mid-core of a hollow construction block) is chosen as a computational testbed. The heterogeneous porous media in the cavity are modelled by unconnected packed beds of equi- and non-equi-sized cylinders. Each cylinder is intelligently placed in the bulk of the natural convection flow to efficiently suppress the momentum in the most energetic regions of the flow. The spatial location of each cylinder is obtained by applying linear stability analysis to the 2D natural convection flow in the presence of the modelled porous media. The flow is treated by using the mesoscale approach, implicitly resolving the flow fields in the vicinity of the immersed cylinders by the immersed boundary method. The results obtained for 2D configurations are validated for realistic 3D flows. Basic statistical evaluation of the generated porous media patterns is performed in order to generalize the developed method of design of "smart" thermo-insulating materials. It is shown that the efficiency of the thermal insulation of the porous medium is closely related to the diameter of the cylinders modelling it. This study comprises an important milestone in the design and manufacture of "smart" thermo-insulating materials from available off-the-shelf porous materials.